School-based Constructive Play focusing on Anxiety and Autism: Evidence from a Novel "Build to PlayTM" Study with Children - Choy, Wai Wan (Trinity College Dublin. School of Education. Discipline of Education, 2024)
This study aims to enhance our understanding of anxiety experiences among 4-6-year-old children, both with and without co-occurring autism, within the context of infant classrooms in Irish schools. Key concepts are defined, with anxiety described as "the persistent feeling of worry, nervousness, or fear that interferes with daily functioning", and autism as "a neurodevelopmental disorder characterised by challenges with social interaction, communication, and repetitive behaviours". Inclusive education aims to remove barriers hindering the participation and achievement of all learners, while early intervention involves providing support and services to children and families as soon as developmental concerns arise. The "Build-to-Play™" programme, developed by the researcher and trademarked in Hong Kong, is a comprehensive intervention to improve children's well-being in educational settings. It includes 14 to 33 weekly children's group sessions of 45 to 60 minutes with flexible adult-to-child ratios (1:2 to 1:4), focusing on nine evidence-based strategies to support social-emotional development. The programme also incorporates whole-class bibliotherapy sessions using storybooks to address themes of anxiety and well-being, enhancing emotional literacy and empathy. Additionally, it engages parents and teachers through consultation and resource packs to foster a collaborative, holistic approach to supporting children's mental health. To address research question one (RQ1) on the risk factors of anxiety disorders, relevant theories such as the Transactional Developmental Model of Anxiety and the Theory of Intolerance of Uncertainty are examined. In tackling RQ2 concerning non-pharmacological peer-mediated play-based interventions, a systematic literature review identifies 34 articles demonstrating effectiveness in anxiety reduction. However, these studies often lack comprehensive support within the bio-ecological context and inclusion by design. Drawing on these theories and the Empathising-Systemising Theory of Autism which focuses on children's strength in construction play, the innovative "Build-to-Play™" programme is developed to address RQ3 regarding its effectiveness in alleviating anxiety in primary education. This thesis comprises a single study with three components, each addressing a sub-research question (RQ3a, b, c). RQ3a is tackled by Component One: Children's Groups, which collects and analyses qualitative and quantitative data from 13 Irish pupils, their peers, parents, and teachers participating in the "Build-to-Play™" programme. Component Two examines the impact of whole-class storybook reading on anxiety understanding and coping with 23 pupils, while Component Three involves 14 parental and six teacher involvement through research instruments of pre- and post-semi-structured interviews, complemented by questionnaires. The methodological approach, informed by a mixed methods design, integrates quantitative and qualitative data collection and analysis. Ethical considerations and the researcher's role are addressed, providing insights into the ethical framework guiding the research. Findings demonstrate an enhanced understanding of childhood anxiety conditions and coping strategies among programme participants, alongside indications of improved support for anxiety and autism in inclusive education settings. The outcomes of these components are thoroughly discussed, considering research questions, theoretical frameworks, and existing literature. Recommendations for educators, parents, and pupils, while acknowledging research strengths and limitations, are proposed, with practical implications and considerations for future research highlighted. In conclusion, the study underscores the pivotal role of early intervention programmes such as "Build-to-Play™" in supporting children with anxiety and autism in inclusive educational environments. It emphasises the importance of evidence-based strategies and collaborative approaches in early intervention practices to enhance outcomes for all learners.
APPROVED
Keywords: Anxiety; Autism; Early Intervention; Inclusive Education; Play